TASAWUF WUJUDIYAH: Hakikat Wujud dalam Ajaran Tasawuf Datu Abulung (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
Discussions about the nature of being have developed into a hot topic of debate between supporters and opponents during Datu Abulung, leading to egregious accusations leveled at those who adhere to this school of thought. They are said to equate God with nature. The explanation in the Resale Sufism book may cause people to misunderstand  ​​the nature of being. Sufism Wujuiyah, which puts forward the idea of ​​the oneness of creatures and God, is clearly understood as a view contrary to the majority's opinion and is seen as such. As a result, the palace was very concerned when Sheikh Abdul Hamid explained this idea to the broader community. This research wants to take an in-depth look at Datu Abulung's Sufism teachings and complement the weaknesses of previous studies. This type of research uses library research. In general, in this library research, data sources are written materials consisting of primary data sources and secondary data sources, while the primary source is from the manuscript of the Resale of Sufism left by Datu Abulung and secondary sources in the form of books and several journals/magazines which contain contains the thoughts of Datu Abulung. The research results show that Datu Abulung's Sufism teachings can be accounted for, and the source is clear from the Qur'an and Hadith. The essence of being in Datu Abulung's Sufism teachings still explicitly recognizes the zahiriyah dualism between the servant and God.Diskusi tentang hakikat wujud telah berkembang menjadi topik perdebatan hangat antara pendukung dan penentang pada masa Datu Abulung, yang mengarah ke tuduhan buruk yang ditujukan pada mereka yang menganut aliran pemikiran ini. Mereka dikatakan menyamakan Tuhan dengan alam. Kemungkinan penjelasan dalam kitab Risalah Tasawuf  yang menyebabkan orang salah memahami gagasan hakikat wujud. Tasawuf wujudiyah yang mengemukakan gagasan tentang keesaan makhluk dan Tuhan, jelas dipahami sebagai pandangan yang bertentangan dengan pendapat mayoritas dan dipandang demikian. Alhasil, pihak istana sangat prihatin ketika Syekh Abdul Hamid memaparkan gagasan ini kepada masyarakat luas. Penelitian kali ini ingin melihat secara mendalam tentang ajaran tasawuf datu Abulung serta melengkapi kekuangan dari penelitian sebelumnya. Jenis penelitian ini menggunakan penelitian pustaka (library research). Secara general, dalam penelitian kepustakaan (library research) ini, sumber data yang merupakan bahan tertulis terdiri atas sumber data primer dan sumber data sekunder, adapun sumber primer dari naskah Risalah Tasawuf peningggalan Datu Abulung dan sumber sukender berupa buku dan beberapa jurnal/majalah yang didalamnya mengandung pemikiran dari Datu Abulung. Hasil penelitian menunjukkan bahwa ajaran tasawuf Datu Abulung bisa dipertanggungjawabkan dan sumbernya jelas dari al-Qur’an dan Hadist. Hakikat wujud dalam ajaran tasawuf Datu Abulung masih secara eksplisit mengakui dualisme zahiriyah antara hamba dan Tuhan.